The Effect of Using Generative AI as Digital Scaffolding on Improving Textual Quality and Narrative Writing Creativity in Indonesian Language Learning in Elementary Schools - Putri Hana Pebriana (Universitas Islam Negeri Palopo, 2025)
Narrative writing is a core component of Indonesian language learning in elementary schools; however, many students experience difficulties in organizing ideas, maintaining coherence, and developing creative storylines. Although digital scaffolding has been widely discussed, empirical evidence on AI-assisted scaffolding in elementary first-language (L1) writing contexts remains limited. This study examined the effect of using Generative AI as digital scaffolding on students’ textual quality and narrative writing creativity. A quasi-experimental pretest–posttest control group design was employed involving 58 upper-grade elementary students (experimental = 29; control = 29). The experimental group received AI-assisted scaffolding across planning, drafting, and revising stages, while the control group received conventional teacher-led scaffolding. Data were collected through narrative writing tasks scored using validated analytic rubrics. Independent samples t-tests and ANCOVA (controlling for pretest scores) revealed that the experimental group achieved significantly higher posttest scores in textual quality (M = 82.41, SD = 6.32) compared to the control group (M = 73.18, SD = 7.05), p < .001, with a large effect size (Cohen’s d = 1.36). Similar significant differences were found in creativity scores (p < .001, d = 1.21). Improvements were most evident in coherence, elaboration, and narrative resolution development. The findings suggest that Generative AI, when used as guided digital scaffolding under teacher supervision, can effectively enhance both structural quality and creative expression in elementary narrative writing. This study contributes empirical evidence to the growing field of AI-assisted writing pedagogy in primary education.